2012
DOI: 10.1002/jmri.23906
|View full text |Cite
|
Sign up to set email alerts
|

In vivo validation of 4D flow MRI for assessing the hemodynamics of portal hypertension

Abstract: Purpose to implement and validate in vivo radial 4D flow MRI for quantification of blood flow in the hepatic arterial, portal venous and splanchnic vasculature of healthy volunteers and patients with portal hypertension. Methods & Materials 17 patients with portal hypertension and 7 subjects with no liver disease were included in this HIPAA-compliant and IRB-approved study. Exams were conducted at 3T using a 32-channel body coil with large volumetric coverage and 1.4mm isotropic true spatial resolution. Usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
103
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 105 publications
(110 citation statements)
references
References 39 publications
5
103
1
1
Order By: Relevance
“…Although pulse sequences for 4D flow MRI continue to be developed, its accuracy and test-retest reliability have been and are constantly seen in various phantom and in vivo studies [17, 24, 5254]. Even though our institution is actively using 4D flow MRI clinically for different complex hemodynamic pathologic abnormalities, the 4D flow MRI techniques used on the clinical cases described in this article are not commonly available on routine clinical MRI systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although pulse sequences for 4D flow MRI continue to be developed, its accuracy and test-retest reliability have been and are constantly seen in various phantom and in vivo studies [17, 24, 5254]. Even though our institution is actively using 4D flow MRI clinically for different complex hemodynamic pathologic abnormalities, the 4D flow MRI techniques used on the clinical cases described in this article are not commonly available on routine clinical MRI systems.…”
Section: Discussionmentioning
confidence: 99%
“…Two-dimensional Doppler ultrasound plays a central role in monitoring patients before and after TIPS placement; however, its limitations make it a suboptimal method to fully characterize the blood flow, not only in the portal system before TIPS but also in the shunt after TIPS to evaluate patency. Four-dimensional flow MRI has been used successfully for monitoring of hepatic blood flow in patients with portal hypertension [20, 24]. …”
Section: Emerging Abdominal Applicationsmentioning
confidence: 99%
“…In 9 healthy subjects measured at two time points, Yzet et al [14] reported PV and HA flow of 15.8/17.1 and 3.2/4.0 mL/s respectively, and corresponding ART of 16.8/19.0%. Recent work reported ART of 16.4 ± 15.8 % in 17 patients with liver cirrhosis using 4D flow imaging [17]. Using dynamic contrast-enhanced (DCE) MRI, Annet et al [30] reported significantly higher portal fraction (100 - ART) in cirrhotic patients (43.81 ± 31.97 vs. 82.58 ± 14.88 for non-cirrhotic liver) and substantial correlation with HVPG (r −0.769, p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…HA circulation was investigated by Wilson et al [19], who reported higher HA flow in 8 patients with PH compared to 9 patients with no PH. Of note, while the measurement of total hepatic blood flow has been studied in healthy volunteers [14, 15], fewer studies have reported concomitant HA and PV flow in subjects with liver cirrhosis using 2D PC MRI [17, 20]. …”
Section: Introductionmentioning
confidence: 99%
“…Baltes et al 10 used retrospective motion correction for navigated 2D cine velocity mapping in coronary flow measurements with gating efficiencies ranging from 17–73%. Bieging et al 32 and Roldán-Alzate et al 33 used bellows for 4D flow MRI with a 50% efficiency in the aorta and the hepatic vasculature, respectively. Self-navigation was used in the aortic 4D flow MRI study by Uribe et al 7 leading to a S eff of 40%.…”
Section: Discussionmentioning
confidence: 99%